Index of orthodontic treatment need of 10-12 years Iraqi pupils (Mustansiria Dental Journal, 2018)
Many orthodontic problems arise at the age of 10-12 years therefore the aim of this study was to detect the percentage of pupil at age 10-12 year that need orthodontic treatment and have not done it till now, and the possibility of motivating them. 1500 Iraqi pupil at school age of 10-12 year were examined according to grade designed by Sweden orthodontic board. 57% of the sample required no treatment, 23.3% required mild treatment, and 14% required moderate while 5.3% required great treatment & 0.3% require very great treatment. Majority of pupils that need treatment didn't receive any motivation even from their dentist, There is a great shortage in dental health education programs. About half of pupil examined didn't need treatment although there is a large number of the sample who needs treatment.